2019
DOI: 10.1016/j.firesaf.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different parameters in the fire behaviour of seven hardwood species

Abstract: Wood is a widely used material in the construction sector, both in structural and nonstructural applications. Tropical species are appreciated for their high quality and durability in furniture, outdoor and indoor claddings and floors. However, limited information exists about fire reaction of tropical wood. Density is one of the factors that influence the rate of pyrolysis reactions and consequently the charring rate. However, other wood characteristics such as the mineral content also exert an influence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
2
8
0
3
Order By: Relevance
“…Two exceptions are observed: residue content increases and decreases significantly respectively for LA and C species. Specific behavior has been already observed for LA [4].…”
Section: Figure 20 -Time To Second Phrr Versus Density For Woods and supporting
confidence: 55%
See 3 more Smart Citations
“…Two exceptions are observed: residue content increases and decreases significantly respectively for LA and C species. Specific behavior has been already observed for LA [4].…”
Section: Figure 20 -Time To Second Phrr Versus Density For Woods and supporting
confidence: 55%
“…Fire behavior of woods has already been investigated using cone calorimeter. As an example, flammability of the Mexican species tested in this study has been reported elsewhere [4]. Briefly, the heat release rate curves exhibit two peaks.…”
Section: Figure 14 -Flexural Modulus Versus Density For All Studied Wmentioning
confidence: 87%
See 2 more Smart Citations
“…Kurva suhu pada kayu kontrol yang meliputi jati, jati-2, meranti merah dan pinus pada uji pembakaran Figure 3. The curves of temperature of control timbers including teak, teak-2, red meranti and pinus in fire test berat jenis yang lebih tinggi, morfologinya yang lebih padat dan kandungan lignin yang lebih tinggi dibandingkan dengan kayu pinus dan kayu meranti merah, memiliki sifat ketahanan terhadap api yang lebih tinggi (Haurie et al 2019). Kenaikan suhu pada kayu jati lebih perlahan dibandingkan kayu pinus dan kayu meranti merah dalam uji pembakaran, seperti yang ditunjukan pada bagian sebelumnya.…”
Section: Waktu Mencapai 260 °Cunclassified